The Role of Openness Personality in Indonesia an Online Marketplace that Influences Online Impulsive Buying Behavior - Rita, Rita; Iswanto, Michella Cecilia (International Journal of Membrane Science and Technology, 2023)
The development of technological innovation in this era has resulted in shopping activities through online marketplaces, which are currently trendy and have shown increasingly high sales, which can be used as the right context to explore consumers' impulsive buying behavior in online marketplaces. The results are only hedonic motives and monetary sales promotions that can significantly influence online impulsive buying behavior partially. Openness personality does not moderate the influence of e-wom, hedonic motives, and monetary sales promotion on online impulsive buying behavior. Suggestions to increase strong online impulsive buying, online stores can use stimulating sales promotion activities that integrate hedonic benefits such as providing promotions when releasing new products.